Outcomes of idiopathic versus secondary nodular regenerative hyperplasia of the liver: A longitudinal study of 167 cases. (28th February 2022) - Penrice, Daniel D.; Thakral, Nimish; Kezer, Camille A.; Lennon, Ryan; Moreira, Roger K.; Graham, Rondell P.; Kamath, Patrick S.; Simonetto, Douglas A.
Abstract: Background: Nodular regenerative hyperplasia (NRH) is a rare condition characterized clinically by the development of non‐cirrhotic portal hypertension. NRH is the histopathological result in the liver of various systemic disease processes including autoimmune disorders, haematological malignancies and medications. However, natural history of this condition has been limited to small case series while patient outcomes pertaining to different aetiologies of NRH are largely unknown. Methods: A retrospective cohort of consecutive patients diagnosed with pathology‐confirmed NRH at Mayo Clinic between 2002 and 2017 was identified. The histological diagnosis of NRH was determined by expert liver pathologists. Patients with metastatic liver disease, history of liver transplantation or younger than 18 were excluded. Potential aetiologies of NRH were classified as haematological, rheumatological, drug‐associated, miscellaneous or idiopathic. Long‐term mortality was analysed using Kaplan‐Meier estimation and Cox regression models. Results: One hundred and sixty‐seven consecutive patients with pathology‐confirmed NRH were analysed over a 15‐year period and followed for a median time of 50 months (1–306 months). The mean age at diagnosis was 53 years. No aetiology or risk factor for NRH was identified in the majority of patients (94, 56.3%), whereas an associated, possibly causal, condition was found in 73 patients (secondary NRH). The most common presenting feature was elevated liver tests (80%), but no significant differences in laboratory tests were seen based on aetiology of NRH. Compared to idiopathic NRH, those with an identified cause had a higher rate of splenomegaly at presentation (54% vs. 27%, p = 0.002). Portal hypertension‐related complications at diagnosis were common, with ascites present in one‐third of patients. Overall transplant‐free survival was 63% at 5 years. Median survival in idiopathic NRH was 9.4 years compared to 7.3 years in secondary NRH. Age, renal function and volume status at presentation were significantly associated with survival; however, MELD score was not. Conclusions: The rates of liver‐related complications and mortality in NRH are low, and only a small number of patients ultimately require liver transplantation. Most patients do not have an identified risk factor or aetiology for NRH, and liver‐related outcomes do not appear to differ based on associated, possibly causal, conditions.